Examining gender as moderating the association between psychopathy and substance abuse - Sellbom, Martin (Psychology, crime & law, 2017)
Previous research has shown a significant association between psychopathy and substance abuse. To date, these associations have not been compared between men and women in forensic or correctional samples, an important topic in light of some empirical findings indicating that psychopathy manifests differently across gender in other contexts. The current study was designed to address this gap in the literature using archival data sets consisting of four large samples derived from forensic, correctional, and university settings, with different measures for psychopathy, alcohol, and substance use. As expected, psychopathy (particularly traits reflective of disinhibition/social deviance) was significantly and moderately correlated with alcohol and substance abuse in all four samples; however, with one minor exception, hierarchical regression analyses revealed no significant moderating effects of gender on these associations. These findings indicate that, although psychopathy may be manifested differently across gender in some ways, substance abuse is likely not one of them.